2016
DOI: 10.1186/s12886-016-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orthokeratology on the progression of low to moderate myopia in Chinese children

Abstract: BackgroundTo investigate the effectiveness of orthokeratology (ortho-k) in reducing the development of myopia in Chinese children with low to moderate myopia.MethodsThis was a retrospective study. In the ortho-k group, there were141 subjects, and the average age was (9.43 ± 1.10) years. The average spherical equivalent refractive error (SER) was (−2.74 ± 1.15)D, with examinations performed 1, 7, 30, and 90 days and 12 months after the patients started wearing ortho-k lenses. In the control group, there were 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
5
25
1
2
Order By: Relevance
“…The magnitude of the treatment-induced power change has also been reported to impact myopia control, independently of baseline myopia, 85 although not in all studies. 71,72,75,86,87 On the other hand, larger pupil diameters, deeper anterior chambers, and steeper, more prolate corneas are among ocular parameters that have been linked to slower axial elongation in children. 88 2.3.5 Visual and Ocular Side Effects.…”
Section: Spectaclesmentioning
confidence: 99%
“…The magnitude of the treatment-induced power change has also been reported to impact myopia control, independently of baseline myopia, 85 although not in all studies. 71,72,75,86,87 On the other hand, larger pupil diameters, deeper anterior chambers, and steeper, more prolate corneas are among ocular parameters that have been linked to slower axial elongation in children. 88 2.3.5 Visual and Ocular Side Effects.…”
Section: Spectaclesmentioning
confidence: 99%
“…This study found that the axial elongation rate of the older children (≥ 13 years old) is slower than that of the younger children (8-10 years old). Studies at home and abroad support that the initial age of OK wearers is negatively correlated with the axial elongation [10][11][12][13][14][15] and consider that the effect of age may be due to the slower eyeball growth of older children. Cho et al proved that OKs can signi cantly reduce the risk of rapid progression of myopia and younger wearer can bene t more in the long term, although younger children have a higher axial growth rate [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have displayed the important role that orthokeratology and multifocal contact lenses can play in the slowing of myopic progression. 8,9 One avenue of treatment currently not used often in the US for myopia control is ophthalmic atropine. Currently, the use of atropine for myopia treatment is not an indication for use approved by the U.S. Food & Drug Administration (FDA) and is considered an "off-label" use in the US.…”
Section: Introductionmentioning
confidence: 99%